Macroautophagy during Innate Immune Activation - Munz, Christian (Frontiers in Microbiology, 2011)
Innate immune activation is initiated by recognition of pathogen associated molecular patterns (PAMPs). Delivery of PAMPs to their respective receptors, regulation of receptor activity and effector functions downstream from these receptors, which constitute part of the initiated innate immune control, are in part mediated via macroautophagy, an evolutionary conserved pathway for cytoplasmic constituent degradation in lysosomes. In this review these facets of the recently unveiled involvement of macroautophagy in innate immunity will be summarized, and aspects that need additional investigations will be high-lighted. The improved understanding of the capabilities of macroautophagy for immunity suggests that this pathway should be harnessed in immunotherapies against infectious diseases.